Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T17:43:03+01:00
3u + 2v = 2 / * (-2)
5u + 4v = 6

-6u-4v=-4
+ 5u+4v=6
-------------
-u=2
u=-2

-6+2v=2
2v=8
v=4

u=-2
v=4



2)
3s + 5t = -6
1,5s - 2t = -3 / * (-2)

3s+5t= - 6
+ -3s+4t=6
-----------------
9t=0
t=0

3s=-6
s=-2

t=0
s=-2


2010-02-02T17:59:50+01:00
3u +2v = 2 /*(-2)
5u + 4v = 6

-6u -4v = -4
5u + 4v = 6
-u = 2 /:(-1)
u = -2

3u +2v = 2 /*(-5)
5u + 4v = 6 /*3

-15u -10v= -10
15u +12v = 18
2v = 8 /:2
v = 4

u = -2
v = 4
_______________________________________________________

3s + 5t = -6
1,5s - 2t = -3 /*(-2)

3s + 5t = -6
-3s + 4t = 6
9t = 0 /:9
t = 0

t= 0
3s + 5t = -6

t=0
3s = 5*0 =-6

t = 0
3s = -6 /:3

t = 0
s = -2